Credit risk in general equilibrium - Eichberger, Jürgen; Rheinberger, Klaus; Summer, Martin (CESifo working papers, 2014)
This paper contributes to the literature on default in general equilibrium. Borrowing and lending takes place via a clearing house (bank) which monitors agents and enforces contracts. Our model develops a concept of bankruptcy equilibrium that is a direct generalization of the standard general equilibrium model with financial markets. Borrowers may default in equilibrium and returns on loans are determined endogenously. Restricted to a special form of mean variance preferences, we derive a version of the Capital Asset Pricing Model with bankruptcy. In this case we can characterize equilibrium prices and allocations and discuss implications for credit risk modeling.